System integration of single seated fuel cell powered vehicle / Buqhari Jaafar - Jaafar, Buqhari (2010)
its power source. This project is entails the study of a complete system integration of the single seated fuel cell powered vehicle. Based on the definition, System integration is the successful putting together of the various components, assemblies, and subsystems of a system and having them work together to perform what the system was intended to do. The objective is to control all subsystems of the vehicle consisting of power train, power plant, braking system, steering system and other subsystem. Scope of this project is to develop the control algorithm for the vehicle system under different driving condition such as acceleration, braking, and steady states condition. However, the objective of the integration is to get optimum performance of the vehicle as product design specifications. The limitation of the integration is the exclusion of aerodynamic and other subsystem such as steering system. Further study should include these steering system and cornering and other subsystem for better control of the vehicle system.